Synthesis and characterization of polyHIPE composites from CTAB-modified halloysite nanotube stabilized Pickering emulsions: Effect of CTAB immobilized nanotube on reducing surfactant usage - Şen, Sinan; Mert, Hatice Hande (İdris Karagöz, 2025)
In this study, halloysite (HL) nanotubes were used as solid particles contributing to the stabilization of high internal phase emulsions (HIPEs) in the preparation of porous composites. PolyHIPEs were obtained by polymerization of the continuous phase of these HIPEs. Immobilization of cetyltrimethylammonium bromide (CTAB) on the HL surface was carried out using the adsorption in solution (SOL) technique. The stability of HIPE without nanofiller was achieved with the use of 5% surfactant by volume. However, the surfactant requirement for the emulsion stability of HIPE materials with organophilic HL fillers (0.25-1.00 wt%) was reduced to 1%. At constant CTAB-SOL-HL clay amounts, decreasing the surfactant concentration resulted in the formation of pores of different sizes, while increasing the amount of filler while keeping the surfactant concentration constant resulted in a decrease in pore size and improved size distribution. The highest adsorption values of cationic dye (Nile Blue) were exhibited by polyHIPE composites containing 0.50 and 1.00 wt% CTAB-SOL-HL, and about 100% more adsorption was obtained with 1% filler compared to pure polyHIPE. The use of CTAB-SOL-HL at 0.50 wt% and above, higher thermal degradation temperatures were achieved in the composites compared to pure polyHIPE. The use of HL nanotubes in the preparation of porous composites is of great importance in terms of possible engineering and environmental benefits in terms of both improving the thermal performance of the materials and taking an active role in the adsorption of the dye, as well as helping to ensure emulsion stability.

Bu çalışmada, haloysit (HL) nanotüpleri, gözenekli kompozitlerin hazırlanmasında yüksek iç faz emülsiyonlarının (HIPE'ler) stabilizasyonuna katkıda bulunan katı partiküller olarak kullanılmıştır. Bu HIPE'lerin sürekli fazının polimerizasyonu ile poliHIPE'ler elde edilmiştir. HL yüzeyine setiltrimetilamonyum bromür (CTAB) immobilizasyonu, çözeltide adsorpsiyon (SOL) tekniği kullanılarak gerçekleştirilmiştir. Nanodolgu ihtiva etmeyen HIPE’nin kararlılığı hacimce %5 surfaktan kullanımı ile sağlanabilmiştir. Bununla birlikte, organofilik HL dolgulu (ağırlıkça %0,25-%1,00) HIPE malzemelerinin emülsiyon kararlılıkları için surfaktan gereksinimi %1’e düşmüştür. Sabit CTAB-SOL-HL kil miktarlarında, surfaktan konsantrasyonunun azaltılması farklı boyutlarda gözeneklerin oluşmasına neden olurken, surfaktan konsantrasyonu sabit tutulduğunda ise dolgu maddesi miktarının artırılması gözenek boyutunda bir azalmaya ve boyut dağılımının iyileşmesine neden olmuştur. En yüksek katyonik boya (Nile Blue) adsorpsiyon değerleri %0,50 ve %1,00 CTAB-SOL-HL içeren polyHIPE kompozitleri tarafından sergilenmiş ve %1 dolgu kullanımı ile saf poliHIPE'ye kıyasla yaklaşık %100 daha fazla adsorpsiyon elde edilmiştir. Ağırlıkça %0.50 ve üzerinde CTAB-SOL-HL kullanımı ile saf polyHIPE’ye nazaran, kompozitlerde daha yüksek ısıl bozunma sıcaklıklarına ulaşılmıştır. Gözenekli kompozitlerin hazırlanmasında HL nanotüplerin kullanımı, emülsiyon stabilitesinin sağlanmasına yardımcı olmasının yanı sıra hem malzemelerin termal performansının iyileştirilmesi hem de boyanın adsorpsiyonunda aktif rol alması açısından olası mühendislik ve çevresel faydalar açısından büyük önem taşımaktadır.
CTAB-modifiye haloysit nanotüp stabilize Pickering emülsiyonlardan poliHIPE kompozitlerinin sentezi ve karakterizasyonu: CTAB immobilize edilmiş nanotüp’ün surfaktan kullanımını azaltmadaki etkisi
2015/DR/061
Keywords: Polymer Science and Technologies; Polimer Bilimi ve Teknolojileri [EN] Polymer Technologies; Polimer Teknolojisi